ROLE OF DIELECTRIC LOSS OF NANOFLUIDS ON OIL RECOVERY MECHANISM UNDER ELECTROMAGNETIC FIELD - ADIL, MUHAMMAD (2018)
Recently, nanoparticles have emerged as a new frontier for improved and enhanced oil recovery (IOR & EOR). Despite their benefits, the particles tend to agglomerate at drastic reservoir conditions which cause their detachment from the oil/water interface, and are consequently retained rather than transported through a porous medium.